2013
DOI: 10.1155/2013/138027
|View full text |Cite
|
Sign up to set email alerts
|

Stress Evaluation in Adult Patients with Atopic Dermatitis Using Salivary Cortisol

Abstract: The symptoms of atopic dermatitis (AD) are often aggravated by stress, and AD can also lead to psychological stress due to social isolation and discrimination. The salivary cortisol level reflects psychological stress, and it is a good index to assess chronic stress. In this study, we measured the salivary cortisol levels in patients with AD (n = 30) and compared them with those of healthy control subjects (n = 42). AD patients were also evaluated for general disease severity using the Scoring Atopic Dermatiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(61 citation statements)
references
References 15 publications
1
54
2
1
Order By: Relevance
“…Cortisol is a steroid hormone (also known as hydrocortisone), produced by the adrenal glands in response to the adrenocorticotropic hormone, and is the final product of the hypothalamic-pituitaryadrenal (HPA) axis [12,14,18,25]. So, cortisol can directly influence the central nervous system, affecting those brain's areas involved in the control of blood pressure [4].…”
Section: Cortisolmentioning
confidence: 99%
See 2 more Smart Citations
“…Cortisol is a steroid hormone (also known as hydrocortisone), produced by the adrenal glands in response to the adrenocorticotropic hormone, and is the final product of the hypothalamic-pituitaryadrenal (HPA) axis [12,14,18,25]. So, cortisol can directly influence the central nervous system, affecting those brain's areas involved in the control of blood pressure [4].…”
Section: Cortisolmentioning
confidence: 99%
“…During stressful situations (acute and chronic stress), the body responds by increasing the production of cortisol, secreted by the adrenal cortex in the HPA axis [14,25]. Circadian rhythm, negative feedback, and stress reactions are known as factors that regulate cortisol secretion [21].…”
Section: Cortisolmentioning
confidence: 99%
See 1 more Smart Citation
“…Current literature offers clear evidence showing that psychological stress affects human immune reactions (Cieslak et al, 2003;Mizawa et al, 2013). Some studies have demonstrated that stress can significantly influence antibody response of vaccinated individuals (Cohen et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…A resposta mais comum a um fator de estresse é a ansiedade, que pode ser entendida como um estado de apreensão, tensão e preocupação (ATKINSON, et al, 1995 O cortisol salivar é capaz de refletir o estresse psicológico (MIZAWA et al, 2013); devido a isso, diversos estudos têm utilizado este marcador como parâmetro fisiológico para avaliação do estresse (MIZAWA et al, 2013;RAGHAVENDRA et al, 2009;BILLHULT et al, 2008). Ainda, a avaliação do cortisol salivar tem se tornado uma alternativa importante, pois o procedimento para coleta das amostras de saliva Adaptar-se às condições estressoras da HD é um processo árduo e o profissional de saúde pode ser de extrema ajuda para auxiliar o indivíduo e sua família neste processo, conhecendo as manifestações de cada um e escolhendo, em conjunto com o paciente, formas alternativas de enfrentá-lo.…”
unclassified